miR-378a-5p represses Barrett’s esophagus cells proliferation, migration and invasion through targeting TSPAN8 - Xie, Xudong; Wei, Duo (Cellular and Molecular Biology, 2024)
Barrett's esophagus (BE) belongs to a pathological phenomenon occurring in the esophagus, this paper intended to unveil the underlying function of miR-378a-5p and its target TSPAN8 in BE progression. GEO analysis was conducted to determine differentially expressed genes in BE samples. Non-dysplastic metaplasia BE samples, high-grade dysplastic BE samples and controls were collected from subjects. CP-A and CP-B cells were exposed to bile acids (BA) to mimic gastroesophageal reflux in BE cells. RT-qPCR as well as western blot were applied for verifying expressions of miR-378a-5p, TSPAN8, CDX2 and SOX9. CCK-8, wound scratch together with Transwell assays were exploited for ascertaining cell proliferation, migration as well as invasion. The targeted relationship of miR-378a-5p and TSPAN8 could be verified by correlation analysis, dual-luciferase reporter experiment, and rescue experiments. Through analyzing GSE26886 dataset, we screened the most abundantly expressed gene TSPAN8 in BE samples. miR-378a-5p was reduced whereas TSPAN8 was elevated in CP-A as well as CP-B cells after triggering with BA. Knocking down TSPAN8 could counteract BA-triggered enhancement in BE cell proliferation, migration along with invasion. miR-378a-5p could suppress BE cell proliferation, and migration along with invasion via targeting TSPAN8. In BE, miR-378a-5p targeted TSPAN8 to inhibit BE cell proliferation, and migration along invasion. miR-378a-5p deletion or elevation of TSPAN8 may be key point in regulating CDX2 and SOX9 levels, thereby promoting BE formation.